(untitled) (Philology, 2019)
The article is centred around the linguistic ethnoimagology which is seen through the reception of Chinese civilization in Bulgarian. The objective of the study is to trace how current, Chinese-oriented lingo-epistemic projections are formed. The study can also be used for determining the dynamics and the creation of stereotypes and concepts, referring to different peoples and cultures. What is more, it can also serve as a starting point in demarcating the leading tendencies as far as the Bulgarian notion of that great country is concerned.